MEMBANGUN KNOWLEDGE MANAGEMENT SYSTEM SEBAGAI SARANA SHARING KNOWLEDGE PADA CV. SOLUSI BERKAH MANDIRI - Liesnaningsih Liesnaningsih (LPPM STMIK ANTAR BANGSA, 2016)
Abstractâ€”Â KnowledgeÂ asÂ oneÂ ofÂ theÂ company'sÂ assetsÂ isÂ oneÂ aspectÂ thatÂ canÂ increaseÂ theÂ valueÂ ofÂ aÂ company'sÂ competitiveÂ advantage.Â KnowledgeÂ becomesÂ importantÂ whenÂ theÂ competitionÂ betweenÂ companiesÂ andÂ laborÂ exchangesÂ happenedÂ soÂ fast,Â itÂ isÂ necessaryÂ forÂ aÂ KnowledgeÂ ManagementÂ SystemÂ inÂ aÂ company.Â ThisÂ thesisÂ entitledÂ